Antibiotics consumption in the Eastern Region Of Libya 2012-2013 - A Khalifa; S Bukhatwa; M Elfakhri (Libyan International Medical University Journal)
Background: Drug utilization studies conducted in Libya during the period 1991-2013, have pointed out the irrational use of antibiotics as a common practice that costs the health system more than 7.7 million Libyan Dinars / year. The aim of this study is to assess the trend of antimicrobial consumption in the Eastern region of Libya during 2012 – 2013. Methods: Antimicrobial consumption data from the years 2012 and 2013 were obtained mainly from Benghazi office, Medical Supply Organization (MSO; the only official drug-importing body in Libya). This study is concerned with antibiotics imported only to the Eastern region of Libya, population of which represents approximately 35% of total Libyan population. The WHO, Anatomical-Therapeutic-Chemical (ATC) classification and the Defined Daily Dose (DDD) methodology were used to calculate antibiotic consumption. The total antimicrobial consumption data were calculated as DDD/1000 inhabitants/day. Results: Total utilization of antibiotics decreased dramatically from 15.47 DDD/1000 inhabitants/day in 2012 to 4.30 DDD/1000 inhabitants/day in 2013 which in turn shows a significant decline compared to 41.72 DDD/1000 inhabitants/day during the period 1991-1993. Consumption of penicillins decreased from 19.902 DDD/1000 inhabitants/day during 1991-1993 to 1.896 DDD/1000 inhabitants/day during 2012-2013 with pattern of amoxicillin/clavulanic acid consumption equals to 3 times ampicillin consumption and is the highest compared to all penicillins. This was accompanied by a prominent increase in consumption of amphenicols and fusidic acid during 2012-2013 noting that fusidic acid consumption was the highest among all antibiotics. Conclusion: MSO since 2011 (post 17th February 2011 revolution) lost its control on importing medicines due to receiving many drugs as donations from different international sources without acceptable level of coordination. This has been reflected on drug purchasing policy of MSO during 2013, which failed to regain the previously accepted level of DDD/1000 inhabitants/day antibiotics consumption. The decreased consumption of penicillins together with increased consumption of amphenicols and fusidic acid complies with the pattern of antibiotic resistance reported previously in Libya. Similar studies should be conducted to evaluate national drug consumption under normal conditions to be compared with regional and international data.